2015
DOI: 10.18632/oncotarget.4814
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 mediates sorafenib resistance of hepatocellular carcinoma cells by inhibiting autophagy via the PTEN/Akt pathway

Abstract: Sorafenib resistance remains a major obstacle for the effective treatments of hepatocellular carcinoma (HCC). Recent studies indicate that activated Akt contributes to the acquired resistance to sorafenib, and miR-21 dysregulates phosphatase and tensin homolog (PTEN), which inhibits Akt activation. Sorafenib-resistant HCC cells were shown to be refractory to sorafenib-induced growth inhibition and apoptosis. Akt and its downstream factors were highly activated and/or upregulated in sorafenib-resistant cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
177
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 191 publications
(184 citation statements)
references
References 44 publications
6
177
1
Order By: Relevance
“…Transfection of miR-21 mimics results in restored sorafenib resistance by inhibiting autophagy in HCC cells. These results demonstrated that miR-21 mediates sorafenib resistance of HCC cells by inhibiting autophagy via the PTEN/Akt pathway [83]. They also suggest that miR-21 could serve as a therapeutic target for overcoming sorafenib resistance in the treatment of HCC.…”
Section: Autophagy and Cancermentioning
confidence: 88%
“…Transfection of miR-21 mimics results in restored sorafenib resistance by inhibiting autophagy in HCC cells. These results demonstrated that miR-21 mediates sorafenib resistance of HCC cells by inhibiting autophagy via the PTEN/Akt pathway [83]. They also suggest that miR-21 could serve as a therapeutic target for overcoming sorafenib resistance in the treatment of HCC.…”
Section: Autophagy and Cancermentioning
confidence: 88%
“…The assay was conducted as described previously [11]. Briefly, the reporter vector plasmid was transfected into cells by using Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…The application of this non-invasive approach may be considered for monitoring responses of lung cancer patients to EGFR-TKI treatment (79). Furthermore, the implication of miR-21 in chemotherapy resistance has been investigated for a wide range of solid cancer types, including pancreatic and prostate cancer, hepatoma, ovarian cancer, glioma, and head and neck, stomach and bladder cancer (Table I) (68)(69)(70)(71)75,(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94). These results support the clinical application of miR-21 inhibition in cancer treatments in the future.…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%